Transcendental Communication as A Form of Self-Healing in The Millennial Generation - Namira Fitria; Grace Heidy Jane Amanda Wattimena; Isa Wijayanti; Ade Budi Santoso; Saiful Romadon (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Humans living in this world cannot be separated from life's problems and trials, which cause emotional wounds and trauma. A healing process or self-healing is needed to eliminate feelings of stress and even depression. Healing is a term used by the millennial generation today. Transcendental communication, where we communicate with God God through worship, can be a way of healing to relieve stress and depression for millennials. This research aims to determine the process of transcendental communication as a form of self-healing in the millennial generation. The research method used is a qualitative approach. Data collection techniques are FGD, observation, and in-depth interviews with informants/participants as primary data. Meanwhile, secondary data uses literature studies sourced from journals, e-books/books, and documents. This research shows that by worshiping and praying to Allah SWT, surrendering all life's problems to Him alone can make the heart and mind calm and clear.